Functional and Structural Benefits Induced by Omega-3 Polyunsaturated Fatty Acids During Aging - Cutuli, Debora (Current Neuropharmacology, 2017)
Background: Omega-3 polyunsaturated fatty acids (n-3 PUFA) are structural components of the brain and are indispensable for neuronal membrane synthesis. Along with decline in cognition, decreased synaptic density and neuronal loss, normal aging is accompanied by a reduction in n-3 PUFA concentration in the brain in both humans and rodents. Recently, many clinical and experimental studies have demonstrated the importance of n-3 PUFA in counteracting neurodegeneration and agerelated dysfunctions. Methods: This review will focus on the neuroprotective effects of n-3 PUFA on cognitive impairment, neuroinflammation and neurodegeneration during normal aging. Multiple pathways of n-3 PUFA preventive action will be examined. Results: Namely, n-3 PUFA have been shown to increase the levels of several signaling factors involved in synaptic plasticity, thus leading to the increase of dendritic spines and synapses as well as the enhancement of hippocampal neurogenesis even at old age. In elderly subjects n-3 PUFA exert anti-inflammatory effects associated with improved cognitive functions. Interestingly, growing evidence highlights n-3 PUFA efficacy in preventing the loss of both gray and white matter volume and integrity. Conclusion: This review shows that n-3 PUFA are essential for a successful aging and appear as ideal cognitive enhancers to be implemented in nutritional interventions for the promotion of healthy aging.
Keywords: omega 3 fatty acids